The Development of Pop Up Book Media with The Character of Art Figure Besutan Jombang - Aurelia, Ifa Dwi; Asmarani, Ratih (IJPSE : Indonesian Journal of Primary Science Education, 2021)
One of the use of learning media is to deliver the material from teacher to students. There are many types of learning media that can be applied to learning activities, especially at the primary school. In the era of technology, there are many new habits in life especially for primary school. Therefore, it is necessary to strengthen the material for primary school students about the value of goodness contained in regional arts. This research is included in research and development which will later obtain the results of a teaching material in the form of a Pop up book learning media by using Jombang's art figures. In addition to obtain a learning media, this research also aims to determine the process, implementation, and quality of the media. The research process was carried out in accordance with the steps in the 4-D model from Thiagarjan which had been modified by researchers without dissemination stage. In the development process, the researcher obtained 94.35% from material and media experts. While at the implementation stage, the researcher obtained 85.89% from the average score given by media users. Then 87.01% for the quality score which is the average of the process and implementation stages which indicates that the media developed by researchers is included in the category of very valid and feasible to be used without the need for improvement.